A concept mapping approach to identifying the barriers to implementing an evidence-based sports injury prevention programme. Issue 4 (20th January 2018) - Donaldson, Alex; Callaghan, Aisling; Bizzini, Mario; Jowett, Andrew; Keyzer, Patrick; Nicholson, Matthew
Abstract : Background and aim: Understanding the barriers to programme use is important to facilitate implementation of injury prevention programmes in real-word settings. This study investigated the barriers to coaches of adolescent female soccer teams, in Victoria, Australia, implementing the evidence-based FIFA 11+ injury prevention programme. Methods: Concept mapping with data collected from 19 soccer coaches and administrators. Results: Brainstorming generated 65 statements as barriers to 11+ implementation. After the statements were synthesised and edited, participants sorted 59 statements into groups (mean, 6.2 groups; range, 3–10 groups). Multidimensional scaling and hierarchical cluster analysis identified a six-cluster solution: Lack of 11+ knowledge among coaches (15 statements), Lack of player enjoyment and engagement (14), Lack of link to football-related goals (11), Lack of facilities and resources (8), Lack of leadership (6) and Lack of time at training (5). Statements in the 'Lack of 11+ knowledge among coaches' cluster received the highest mean importance (3.67 out of 5) and feasibility for the Football Federation to address (3.20) rating. Statements in the 'Lack of facilities and resources' cluster received the lowest mean importance rating (2.23), while statements in the 'Lack of time at training' cluster received the lowest mean feasibility rating (2.19). Conclusions: A multistrategy, ecological approach to implementing the 11+—with specific attention paid to improving coach knowledge about the 11+ and how to implement it, linking the 11+ to the primary goal of soccer training, and organisational leadership—is required to improve the uptake of the 11+ among the targeted coaches.